Modeling nonlinear behavior of band-pass memoryless and dynamic systems - Pedro, J.C.
This paper addresses nonlinear distortion arising in microwave band-pass memoryless and dynamic systems. It first identifies the minimum requirements for their correct representation. Then, it shows that the complex behavior of long term memory effects does not allow a unique characterization procedure, but demands for various nonlinear distortion figures according to the type of nonlinear RF impairments the actual system is sensitive to.